The critical driving and success factors for the successful implementation of AI for businesses in the retail industry - Naeem, Mir Fawwaz (2025)
Artificial Intelligence (AI) is revolutionizing businesses worldwide and the retail industry is one of the major adopters. However, retailers are struggling to implement AI into their businesses with sustainable success. There are several complex elements tied to implementing and integrating AI within an organisation's ecosystem. This explorative research aims to uncover the critical success factors for successful AI implementation within retail businesses. Qualitative research was conducted through semi-structured interviews with AI experts who had prior retail-related and implementation experience. The research finds 67 critical success factors and categorises them into relevant groups including strategic, organisational, technical, human, ethical and external. The identified factors were scored by the interview participants in terms of significance through a 5-point Likert scale system. The results highlight the “alignment of AI with business goals” and “understanding a customer's problems and delivering business impact” as the most significant success factors for AI implementation in retail. These are followed by the importance of obtaining senior executive buy-in, adequately preparing data for high quality, using cost-effective approaches, continuously monitoring and retraining models and ensuring the ethical use of AI. Aside from a comprehensive list of factors, this study provides a guiding framework to help retail decision-makers prioritise key elements for AI in their implementation journey. For academia, it adds to the existing literature on critical success factors for AI implementation while also providing retail-industry-specific insights.